METHODS AND CONDITIONS FOR EFFECTIVE MASTERING PRINCIPLES OF GYMNASTICS - Kenjayeva Sayyora Xudaybergenovna (European International Journal of Pedagogics, 2024)
This article describes the methods and conditions for effective mastery of gymnastic exercises using the principles of successful organization of gymnastic exercises.